2017
DOI: 10.1071/an141037
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat properties of six genotypes of young bulls finished under feedlot tropical conditions of Mexico

Abstract: The effect of six genotypes (Zebu = Z, European Brown Swiss = EBS, Holstein = H, Z × EBS, Zebu × American Brown Swiss = ABS, Z × ABS, Z × H) on carcass and meat characteristics of young bullocks finished under feedlot conditions was tested. The Z × ABS bullocks had the highest (P = 0.001) average daily gain. The highest (P = 0.017) final liveweight was observed with Z × ABS > EBS > H genotypes. The ribeye area was larger (P = 0.012) for EBS bullocks. Both H and EBS bullocks had lowest (P = 0.001) physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The results of the present trial agree with other reports reporting carcass grades for fed entire males where the "Bulls" of "Bullocks" with Bos indicus influence, hardly exceeded the USDA-Standard grade, but exhibited the top USDA yield grades [16,36].…”
Section: Carcass Classification/grading Of the Experimental Groupssupporting
confidence: 92%
“…The results of the present trial agree with other reports reporting carcass grades for fed entire males where the "Bulls" of "Bullocks" with Bos indicus influence, hardly exceeded the USDA-Standard grade, but exhibited the top USDA yield grades [16,36].…”
Section: Carcass Classification/grading Of the Experimental Groupssupporting
confidence: 92%
“…In Mexico, young feedlot-finished bulls of six genotypes (zebu, European Brown Swiss, Holstein, zebu × European Brown Swiss, zebu × American Brown Swiss and zebu × Hereford) showed few significant differences in carcass and meat characteristics [ 78 ]. Of note was the higher shear force of the zebu (80 N) than all other genotypes (61–68 N).…”
Section: Carcass and Meat Qualitymentioning
confidence: 99%
“…Lower IMF content was reported in Brahman than Charolais bulls (2.4% vs. 2.9%) [ 74 ], and in 25-month-old Nellore steers (2.65%) compared to Santa Gertrudis × Nellore crosses (3.64%), while the IMF content of Simmental × Nellore steers was intermediate and not different from either [ 105 ]. Two studies found no differences in IMF contents, both reporting low values (1.3–2.0% IMF) [ 66 , 78 ]. In one of these studies, the breeds were not reported [ 66 ], while in the other bulls of zebu, Holstein and European Brown Swiss purebreds and zebu crosses with Holstein, American Brown Swiss or European Brown Swiss were used.…”
Section: Nutrient Compositionmentioning
confidence: 99%
“…Prior to the analysis of cooking losses (CL) and Warner-Bratzler shear force (WBSF), the samples were thawed for 24 h at 4 • C in a cooler protected from drafts and the meat samples were analysed in triplicate. CL was determined according by Vazquez-Mendoza et al [33]; for this purpose, fillets with 2.5 cm thick were roasted on a grill (Toastmaster cool-edgegrill, Macon, MO, USA) until they reached an internal temperature of 70 • C, which was monitored with a thermometer (Brannan & Sons, Cleator Moor, Cumbria, UK). When the temperature reached 70 • C, the fillets were removed from the grill and allowed to cool to room temperature (20-25 • C).…”
Section: Meat Qualitymentioning
confidence: 99%
“…When the temperature reached 70 • C, the fillets were removed from the grill and allowed to cool to room temperature (20-25 • C). To calculate the percentage of CL, each fillet was weighed before and after the procedure (weight of raw meat−weight of cooked meat)/weight of raw meat ×100), as it was described by Vazquez-Mendoza et al [33]. In order to measure the WBSF, 2.5 cm thick meat fillets (three per lamb) were cooked at 70 • C using the CL method, as sited above.…”
Section: Meat Qualitymentioning
confidence: 99%